Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1046/j.1440-1754.1999.355406.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the potential for opportunistic vaccination in a Northern Territory hospital

Abstract: There were numerous missed opportunities to vaccinate children in hospital, especially in the ED. Simple prompts improved documentation of vaccination status and the detail of information recorded. Despite improved documentation, opportunistic vaccination failed to improve in the ED. Improving documentation of vaccination status is not sufficient in itself to improve opportunistic vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…Although presentation to community clinics during the first year of life is almost universal [6], this does not translate to either timely or complete immunization in this population [13,14]. Opportunistic immunization among hospitalized children is poor [15], and the ongoing management of children in need of follow-up after hospital discharge is inadequate [16], which suggests that hospitalization does not improve immunization status. Furthermore, among hospitalized children in the NT, there was no difference over the study period in 7vPCV vaccine coverage between children with and children without comorbidities of gastroenteritis, anemia, and/or malnutrition [4].…”
Section: Discussionmentioning
confidence: 99%
“…Although presentation to community clinics during the first year of life is almost universal [6], this does not translate to either timely or complete immunization in this population [13,14]. Opportunistic immunization among hospitalized children is poor [15], and the ongoing management of children in need of follow-up after hospital discharge is inadequate [16], which suggests that hospitalization does not improve immunization status. Furthermore, among hospitalized children in the NT, there was no difference over the study period in 7vPCV vaccine coverage between children with and children without comorbidities of gastroenteritis, anemia, and/or malnutrition [4].…”
Section: Discussionmentioning
confidence: 99%
“…1 The low rates of documentation in the ED are in stark contrast to a study that found that 98% of patients admitted to an Australian inpatient paediatric unit had their immunisation status recorded. 2 The most frequent recorded parameters were weight and immunisation status.…”
Section: Dear Editor Paediatric Assessment In a General Metropolitanmentioning
confidence: 88%
“…3,4 In particular, Skull et al found that immunisation status was 2.2 times more likely to be recorded when a visual prompt was used. 1 When they combined visual prompts with staff education, they were able to improve immunisation status documentation from 24% to 46%.…”
Section: Dear Editor Paediatric Assessment In a General Metropolitanmentioning
confidence: 99%
“…The burden of meeting these targets has traditionally been left with professionals in a primary care role. Although some countries have demonstrated reasonable success with delivering immunisations in this setting, studies have put forward the potential of OI in a secondary care environment 5–9,16,17 …”
Section: Discussionmentioning
confidence: 99%
“…Although some countries have demonstrated reasonable success with delivering immunisations in this setting, studies have put forward the potential of OI in a secondary care environment. [5][6][7][8][9]16,17 Despite policies clearly advocating OI, 16,18 some members of the paediatric profession do not perceive that immunisations and their delivery are part of their role or that it should not be a focus of hospital care. 16 Our data demonstrate that children in contact with secondary health services have lower immunisation rates than the general population, and support the view that immunisation is part of the clinical duty of care to patients, regardless of setting.…”
Section: Discussionmentioning
confidence: 99%